Numerical Study on Laminar-Turbulent Transition Flow in Rectangular Channels of a Nuclear Reactor - Wang, Zhenying; Zhang, Rui; Yu, Ting; Liu, Zhiyun; Huang, Yu; Wang, Jianjun; Cong, Tenglong (Frontiers in Energy Research, 2020)
Laminar-turbulent transition flow can be observed in the thermal engineering applications, while the flow resistance and heat transfer characteristics were not fully understood. In this work, the flow and heat transfer for laminar-turbulent transition in the rectangular channel were predicted by a four-equation transition turbulent model. A set of correlations for heat transfer coefficient in the rectangular channel were developed and implemented into the RELAP5/MOD3.1 code to make it capable for the analysis of plate-type fuel assembly with rectangular coolant channel. The improved RELAP5/MOD3.1 code was employed to analyze the SBLOCA along with SBO scenario for an integrated pressurized reactor, illustrating the effects of model modification on the evolution of the accident.